Finite Element Analysis of Reinforced Concrete Beams with Corrosion Subjected to Shear - Tanarat Potisuk; Christopher C. Higgins; Thomas H. Miller; Solomon C. Yim (Advances in Civil Engineering)
Finite element (FE) modeling techniques were developed to isolate the different contributions of corrosion damage to structural response of experimental reinforced concrete beams with shear-dominated behavior. Corrosion-damage parameters included concrete cover spalling due to the expansion of corrosion products; uniform stirrup cross-sectional loss from corrosion; localized stirrup cross-sectional loss due to pitting; debonding of corrosion-damaged stirrups from the concrete. FE analyses were performed including both individual and combined damages. The FE results matched experimental results well and quantitatively estimated capacity reduction of the experimental specimens.